Stepwise interview with private sector - Olam (U) Ltd - Mr. Roy Okumu - Margiotta, S. (International Institute of Tropical Agriculture, 2019)
Interview with Olam (U) Ltd Mt Elgon Zonal Manager, highlighting the advantages of Olam collaboration with IITA, and the benefits of the Stepwise approach to resource constrained farmers in the region.